2023
DOI: 10.3390/nu15102400
|View full text |Cite
|
Sign up to set email alerts
|

Leucine and Glutamic Acid as a Biomarker of Sarcopenic Risk in Japanese People with Type 2 Diabetes

Abstract: This study aimed to identify the serum metabolites associated with sarcopenic risk in Japanese patients with type 2 diabetes, determine the effect of dietary protein intake on the serum metabolic profile, and examine its association with sarcopenia. Ninety-nine Japanese patients with type 2 diabetes were included, and sarcopenic risk was defined as low muscle mass or strength. Seventeen serum metabolites were quantified after gas chromatography–mass spectrometry analysis. The relationship between dietary prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Concurrently, our data suggest a correlation between serum L-glutamate concentration and SMI. This is in line with previous investigations showing that glutamate is crucial in maintaining the homeostasis of energy metabolism in skeletal muscle [ 93 ]. Surprisingly, this relationship was observed in the non-frail but not in the frail group, suggesting that different biological pathways may modulate the maintenance of skeletal muscle mass across healthy and frail aging.…”
Section: Discussionsupporting
confidence: 93%
“…Concurrently, our data suggest a correlation between serum L-glutamate concentration and SMI. This is in line with previous investigations showing that glutamate is crucial in maintaining the homeostasis of energy metabolism in skeletal muscle [ 93 ]. Surprisingly, this relationship was observed in the non-frail but not in the frail group, suggesting that different biological pathways may modulate the maintenance of skeletal muscle mass across healthy and frail aging.…”
Section: Discussionsupporting
confidence: 93%
“…GTRAP3-18 regulates glutamate transport as a negative regulator of EAAT3 function . Glutamate is not only crucial for energy metabolism, amino acid transport, protein biosynthesis, and neurotransmitter transmission but also has been identified as a biomarker and potential therapeutic target for sarcopenia in type 2 diabetes patients . Furthermore, our results found that DP increased the expression of Trim54 protein in the gastrocnemius of diabetic mice.…”
Section: Discussionmentioning
confidence: 49%
“…Certain early studies found that the ratio of serum branched-chain amino acids to histidine may have potential clinical use as a KOA biomarker [ 77 ]; very recently, certain studies revealed that the serum levels of leucine and glutamic acid are potential biomarkers and are associated with a higher sarcopenic risk in individuals with type 2 diabetes [ 78 ].…”
Section: Resultsmentioning
confidence: 99%